Into the classroom : the Outward Bound® approach to teaching and learning - Sakofs, Mitchell S. (Kendall/Hunt, 1996)
"This book is about bringing joy and adventure to teaching and learning." Activities and lessons for use with students to build community, cultivate compassion and moral conviction, nurture leadership, teach academics and equip them with the skills to be lifelong learners. Includes a discusssion of Outward Bound philosophies and principles. Some curriculum relates directly to academic studies: culture, nature, geography, language arts. Emphasis is on challenging students to make choices, take responsible action, acquire new skills and working together.